2015
DOI: 10.1117/1.jbo.20.7.075002
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a method to measure light distortion surrounding a source of glare

Abstract: Our objective was to validate a new device dedicated to measure the light disturbances surrounding bright sources of light under different sources of potential variability. Twenty subjects were involved in the study. Light distortion was measured using an experimental prototype (light distortion analyzer, CEORLab, University of Minho, Portugal) comprising twenty-four LED arrays panel at 2 m. Sources of variability included: intrasession and intersession repeated measures, pupil size (3 versus 6 mm), defocus (+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…The authors suggested that larger pupils were associated with stronger disturbances, but pupil size by itself was found to be only moderately correlated with this worsening effect in those eyes presenting positive SA as a consequence of the surgical procedure. More recently, Ferreira-Neves et al 9 evaluating nonoperated eyes showed that changing the pupil size from 3 to 6 mm did not have a significant impact on LD in healthy subjects with pharmacologically paralyzed accommodation. At first, this seems to imply that pupil size has no significant effect on light disturbance and accommodation might be involved.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The authors suggested that larger pupils were associated with stronger disturbances, but pupil size by itself was found to be only moderately correlated with this worsening effect in those eyes presenting positive SA as a consequence of the surgical procedure. More recently, Ferreira-Neves et al 9 evaluating nonoperated eyes showed that changing the pupil size from 3 to 6 mm did not have a significant impact on LD in healthy subjects with pharmacologically paralyzed accommodation. At first, this seems to imply that pupil size has no significant effect on light disturbance and accommodation might be involved.…”
Section: Discussionmentioning
confidence: 98%
“…8 LD was analyzed with an experimental prototype, the LDA (CEORLab, University of Minho, Portugal), which provides a comprehensive number of metrics to characterize the condition, and proved to be robust in measuring NVD in young healthy eyes and also in elderly patients. 3,8,9 It consists of an electronic black board with a central light source (LED) surrounded by 240 small LED sources distributed in 24 semimeridians with a minimum angular separation of 15 deg. In this experiment, an angular separation of 30 deg was considered to shorten the exam time without significant loss of information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of an array of 240 1 mm wide LEDs distributed radially at 15° intervals over 160 mm, with a linear separation of 10 mm around a central 5 mm white LED that acts as glare source, as previously described [17, 18, 20]. The system is controlled by a custom-made software that interfaces with the patient to detect the peripheral stimuli seen and discriminate them from those hidden by the central glare source.…”
Section: Methodsmentioning
confidence: 99%
“…We use a physical display to present the stimuli as this allows us to have a wider dynamic range of luminance from the main glare source and the detection peripheral stimuli [20] and this instrument has been shown to be consistent with [17] and sensitive to changes in higher-order aberrations (HOA) artificially induced [18]. …”
Section: Introductionmentioning
confidence: 99%